Strategy for Developing Ecotourism in the Imbo Putui Customary Forest Petapahan, Tapung District, Kampar Regency, Riau - Riani, Imelda; Sumiarsih, Eni; Syafii, Muhammad (Lembaga Penelitian dan Pengabdian Kepada Masyarakat Universitas Riau, 2025)
Forests are important in human life because they have ecological, social, and economic functions. One way to utilise forest environmental services to preserve the environment and increase income is to manage them as ecotourism sites. One area with ecotourism potential that needs to be developed in Kampar Regency is the 251-hectare Imbo Putui Customary Forest. Despite its diverse potential, the development of Imbo Putui Customary Forest Ecotourism faces several challenges, such as human resources for management and tourism infrastructure facilities. The location of this study is the Imbo Putui Petapahan Customary Forest Ecotourism site. This study aims to analyse the existing ecological, social, and economic conditions of the Imbo Putui Customary Forest Ecotourism potential and formulate a development strategy for the Imbo Putui Petapahan Customary Forest Ecotourism. This study uses a mixed methods approach with a qualitative dominance. Primary data was collected directly from the field through interviews, questionnaires, and observations. The existing conditions were measured using purposive sampling and qualitative descriptive analysis. Meanwhile, the ecotourism development strategy was formulated using SWOT analysis. The analysis results show that the strategic position for implementing Imbo Putui Customary Forest Ecotourism is quadrant I, namely the S-O (Strengths-Opportunities) strategy. The strategies that can be applied are to develop integrated tourism packages based on attractions, activities, and digital promotion; utilise local wisdom and area zoning as ecotourism educational material; optimise forest legality to expand stakeholder cooperation and program support; and make tree diversity and flora and fauna protection the basis for educational tourism and research.